(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Federalism is a system of government in which power is divided between state and national levels. Indian constitution adopted the model of federal system based on Canadian model of federal system.The paper discussed about the problem in Indian federal system. The paper is an attempt to analyse the challenge to Indian federal system like demands for new states, demands for autonomy and re- define the centre state relations.